Effect of plant growth regulators in the in vitro multiplication and rooting of senecio calvus (Asteraceae), high-andean medicinal plant, endemic to Peru - Laguna-Ibarra, Yenilda (2020)
In vitro propagation of Senecio calvus was carried out as an alternative for its conservation. The buds were disinfected with HgCl2 (0.01 and 0.1%) with and without periodic addition of antibiotics. Murashige and Skoog culture medium (1/2) plus 2% sucrose and 0.3% phytagel 0.3%, and pH 5.7 was supplemented with benzylaminopurine for multiplication; while for the rooting naphthaleneacetic acid or gibberellic acid were used. Treatments without growth regulator were added. For acclimation two natural substrates were evaluated. The highest percentage of disinfection was obtained with 0.1% HgCl2 for 5 minutes adding rifampicin (72 μg·mL-1) and nystatin (200 μg·mL-1) every three days per 18 days. Benzylaminopurine increased the survival of the introduced buds and the percentage of shooted plants; however the number of shoots per plant did not show significant differences. Gibberellic acid had a positive effect on rooting while naphthaleneacetic acid induced callusing formation. The best substrate for acclimatization was soil + moss (1: 1).